What goes around comes around: The integrated role of emotions on consumer ethical decision‐making - Escadas, M. (2020)
The current study aims to further our understanding of the integrated role of emotions on consumer decision-making involving ethical issues, by considering the influence of both positive and negative emotions on ethical decision-making process. It considers not only the emotions experienced prior to ethical decision-making (pre-decision emotions) but also those resulting from the course of action chosen (post-decision emotions). Scenarios are used, and the results of the structural modelling analyses support the proposed relationships between current emotions, consumers' ethical decision-making, post-decision emotions and future ethical behavioural intentions. The data suggest the possible existence of a “virtuous ethical cycle”, whereby positive emotions lead to more ethical consumer decisions and behaviours; and these in turn lead to more positive (post-decision) emotions, which have a positive and significant effect on future ethical behavioural intentions. In addition, happiness emerges as exerting a pivotal role in predicting consumer ethical decisions.